Peranan Image of Company, Image of User dan Image of Product dalam Meningkatkan Rating Box Office Film Dilan - Susan Purnama; Fitri Reyta; Bob Foster; Muhamad Deni Johansyah (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
The 1990 Dilan film became a boom in early 2018, compared to the previous film, the film by Fajar Bustomi became a breakthrough by lifting the 1990 time setting and successfully seized the attention of the audience. As of aired from January 25, 2018, until 7 February 2018, the number of ticket sales has reached 4.3 million and earned a box office income of Rp. 250 billion. This success does not escape the marketing strategy. Netizens began to question how the marketing strategy carried out by the production team so that this film could attract many viewers in a short time. The purpose of this study is to find out what marketing strategies make consumers want to watch Dilan 1990 films, whether there is a connection with the image of company (film manufacturer), the image of the film actor Dilan (actor) or image of the film Dilan 1990 itself. The study was conducted with a quantitative approach, the population was taken from the 1990 Dilan film consumers in the city of Bandung and the samples were taken as many as 100 film viewers randomly. The testing technique conducted to test samples used Partial Least Square techniques, the results of this study revealed that 43.55% brand image played a role in increasing the box office rating. The quality of products, content, performers and film production houses is able to increase interest in watching in the city of Bandung, the majority of respondents are women aged 15-25% and work as students.